Hepatitis C virus-associated neurocognitive and neuropsychiatric disorders: Advances in 2015 - Monaco, Salvatore; Mariotto, Sara; Ferrari, Sergio; Calabrese, Massimiliano; Zanusso, Gianluigi; Gajofatto, Alberto; Sansonno, Domenico; Dammacco, Franco (World journal of gastroenterology : WJG, 2015)
Since its identification in 1989, hepatitis C virus (HCV) has emerged as a worldwide health problem with roughly 185 million chronic infections, representing individuals at high risk of developing cirrhosis and liver cancer. In addition to being a frequent cause of morbidity and mortality due to liver disease, HCV has emerged as an important trigger of lymphoproliferative disorders, owing to its lymphotropism, and of a wide spectrum of extra-hepatic manifestations (HCV-EHMs) affecting different organ systems. The most frequently observed HCV-EHMs include mixed cryoglobulinemia and cryoglobulinemic vasculitis, B-cell non-Hodgkin's lymphoma, nephropathies, thyreopathies, type 2 diabetes mellitus, cardiovascular diseases, and several neurological conditions. In addition, neuropsychiatric disorders and neurocognitive dysfunction are reported in nearly 50% of patients with chronic HCV infection, which are independent of the severity of liver disease or HCV replication rates. Fatigue, sleep disturbance, depression and reduced quality of life are commonly associated with neurocognitive alterations in patients with non-cirrhotic chronic HCV infection, regardless of the stage of liver fibrosis and the infecting genotype. These manifestations, which are the topic of this review, typically occur in the absence of structural brain damage or signal abnormalities on conventional brain magnetic resonance imaging (MRI), although metabolic and microstructural changes can be detected by in vivo proton magnetic resonance spectroscopy, perfusion-weighted and diffusion tensor MRI, and neurophysiological tests of cognitive processing. Several lines of evidence, including comparative and longitudinal neuropsychological assessments in patients achieving spontaneous or treatment-induced viral clearance, support a major pathogenic role for HCV in neuropsychiatric and neurocognitive disorders.